2009
DOI: 10.1111/j.1365-2109.2008.02105.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfamerazine on selected haematological and immunological parameters in rainbow trout (Onchorhynchus mykiss, Walbaum, 1792)

Abstract: In the present study, e¡ects of sulfamerazine on some haematological and immunological parameters of rainbow trout (Oncorhynchus mykiss) were examined. Four groups of rainbow trout were fed experimental diets containing either no sulfamerazine (control) or supplemented with sulfamerazine at 100 mg kg À 1 (Exp-A), 200 mg kg À 1 (Exp-B) or 400 mg kg À 1 (Exp-C) for 21days. Blood samples were taken for the haematological and immunological parameters from ¢sh on the third, seventh, 14th and 21st days of feeding. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 36 publications
3
28
0
1
Order By: Relevance
“…A decrease in the blood plasma total protein concentration was also ascertained . Similar results were also reported by other authors (Srivastava et al, 1995;Tanck et al, 1995;Saglam et al, 2003). A long-term exposure of African walking catfish (Clarias gariepinus) to malachite green caused anaemia and a reduction in the number of neutrophil granulocytes (Musa and Omoregie, 1999).…”
Section: Side-effects On Treated Fish and Fish Eggssupporting
confidence: 80%
“…A decrease in the blood plasma total protein concentration was also ascertained . Similar results were also reported by other authors (Srivastava et al, 1995;Tanck et al, 1995;Saglam et al, 2003). A long-term exposure of African walking catfish (Clarias gariepinus) to malachite green caused anaemia and a reduction in the number of neutrophil granulocytes (Musa and Omoregie, 1999).…”
Section: Side-effects On Treated Fish and Fish Eggssupporting
confidence: 80%
“…The immunomodulating effects of antibacterial drugs are numerous and variable and depend on the drug used [5]. The interaction of drugs with lymphoid tissues may alter the functions and balance of the immune system and induce undesirable effects, such as immunosuppression, uncontrolled cell proliferation, alterations of other host defence mechanisms against pathogens, and even neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced leucocyte proliferation in vitro but not in vivo has been shown in rainbow trout (Oncorhynchus mykiss) after treatment with different sulfonamides combined with TMT (Grondel et al 1986;Lunden and Bylund 2002). Saglam and Yonar (2009) found decreases in haematological (haematocrit and leucocrit values, and haemoglobin), and immunological parameters (total plasma protein and total Ig levels) in the same fish species treated with sulfamerazine. This study also showed that sulfamerazine had an immunosuppressive effect on fish because of a decrease in NBT(+) cell levels.…”
Section: Introductionmentioning
confidence: 88%